Multi-omics approaches for the understanding of therapeutic mechanism for Huang-Qi-Long-Dan Granule against ischemic stroke - Chuanhong Wu; Chaoyong Wu; Lixia Peng; Mingxuan Wu; Zhiqiang Li; Jianxin Chen (Elsevier, 2024)
After long-term clinical application, traditional Chinese medicine (TCM) has accumulated rich experience in the stroke treatment. Huang-Qi-Long-Dan Granule (HQLDG) is a TCM formula that has been used in clinical for the treatment of acute ischemic stroke. However, its mechanism against ischemic stroke is still unknown. This study aimed to identify HQLDG's effect against ischemic stroke and explore its underlying mechanism. 16s rRNA sequencing, metabolomics/tryptophan (Trp)-targeted metabolomics analysis and transcriptomic analysis were used to investigate HQLDG underlying therapeutic mechanism. Our results revealed that HQLDG significantly decreased the infarct volume, improved mouse behavior and brain slices pathological staining. In addition, it could ameliorate intestinal barrier damage and regulate tight junction gene expression. 16s rRNA, metabolomics and transcriptomics analysis revealed that HQLDG treatment significantly improved the composition of gut microbiota and Trp metabolism pathway, and further downregulated Th17/IL-17 signaling pathway. HQLDG treatment could significantly decrease serum inflammatory cytokines, IL-17A and IL-22; down-regulate Trp metabolism receptor gene (Ahr), inflammatory cytokines genes (IL-17a, IL-22), and an important coding gene for maintaining the mature Th17 (rorc) in both brain and intestinal tissues. In the contrary, after gut microbiota removal, this effect of HQLDG was impaired. HQLDG treated mouse fecal microbiota transplantation also had positive effect against tMCAO injury. Moreover, AhR inhibitor could decrease IL-17A immunofluorescence. These results suggested that the gut microbiota regulation might be an important intermediate in HQLDG against tMCAO injury. HQLDG might exert anti-ischemic stroke effects through the gut microbiota-Trp metabolism-Th17/IL-17 signaling, which provides new insights into HQLDG-mediated prevention in ischemic stroke.